1996
DOI: 10.1016/0029-7844(95)00374-6
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence and Very Low Birth Weight Infants: A Disproportionate Association

Abstract: Preterm birth is one of the major unresolved problems in modern obstetrics. Although the association between adolescence and preterm birth has been reported previously, specific attention has not been focused on the VLBW neonate. We conclude that adolescents deliver a disproportionate number of VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 17 publications
1
19
0
4
Order By: Relevance
“…[1][2][3][4] Causes for the poorer birth outcomes in adolescents have been ascribed to lower rates of adequate prenatal care, 5 poor weight gain and nutrition, 6 higher rates of tobacco use, high-risk health behaviors, 7 and socioeconomic background characteristics. 8 For the most part, teen pregnancy and childbearing studies refer to 15-19-year-old mothers and do not often include childbearing in adolescents ,15 years old.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Causes for the poorer birth outcomes in adolescents have been ascribed to lower rates of adequate prenatal care, 5 poor weight gain and nutrition, 6 higher rates of tobacco use, high-risk health behaviors, 7 and socioeconomic background characteristics. 8 For the most part, teen pregnancy and childbearing studies refer to 15-19-year-old mothers and do not often include childbearing in adolescents ,15 years old.…”
Section: Introductionmentioning
confidence: 99%
“…growth-restricted infants (4,13,16,38). Biological immaturity due to young maternal age and continued maternal growth have been implicated as causal factors of teenagers' susceptibility (12-14, 40, 45).…”
mentioning
confidence: 99%
“…More number of unbooked cases usually due to low socioeconomic status and illiteracy of patients PIH, Anemia, Abruptio placenta, PROM, Oligohydramnios were observed in higher percentage among teenage pregnancies when compared to primigravida within the age group of 20-29 years. Bhattacharya A et al [12], Bhalerao AR et al [13], Miller HS et al [14], Jacono JJ et al [15] observed that more antenatal complications among teenage pregnancies when compared to primigravida with in the age group of 20-29 years. Anemia (67.8%) was the most commonly observed complication in both groups followed by PIH which was 29.2%.…”
Section: Discussionmentioning
confidence: 99%